Elaboration of a biotic index of pollution using macro-invertebrates for the monitoring of Lake Nokoue in Benin - GNOHOSSOU, Pierre; LALEYE, PHILIPPE A. (My University, 2015)
A study on the relationships between the physicochemical parameters and of the macroinvertebrates of the Lake Nokoué was carried out for the purpose of developing a biotic index of pollution. A total of 96 stations were prospected twice during the flooding and the dry seasons from September 2004 to February 2006. At each station, seven physicochemical parameters were measured and macroinvertebrates were collected. Canonical analyses of correspondence were used to show the relations between the parameters of the environment and the macroinvertebrates. A self-organizing map (SOM) of Kohonen allows the categorization of the studied stations into four groups according to different degrees of pollution. Rough scores were allotted to each taxon according to its abundance in the various groups of stations determined by the SOM for each campaign. A synthesis of the data obtained from the four field surveys allows the assignment of a score to each taxon according to its abundance in the different groups of stations. A biotic index was developed and used for the evaluation of the level of pollution of the stations studied. It then emerged that the borders of the lake present a «poor quality» of water; however, during the dry season there is slight improvement. © 2015 International Formulae Group. All rights reserved.
Keywords: Biotic index; pollution; invertebrates; lagoons; Benin; West Africa.